Cost-Return Budgets–Irrigated Crops - Dhuyvetter, Kevin C.; Whitney, David A. (My University, 2000)
This publication utilizes specific input values and/or rates for seed, insecticide, herbicide, and fertilizer based on a given yield level to provide information for producers with irrigated crops.
MF941_2000_10
Keywords: MF941; Economics; Crops; MF